PENGARUH LAMA WAKTU PENUMBUHAN SECARA VIBRASI TERHADAP STRUKTUR, KAPASITAS TUKAR KATION DAN INDEX SWELLING BETONIT - Tasrif Tasrif; Siti SP Isnijah (Research Center for Chemistry - LIPI, 1999)
Bentonite is a kind of mining products, which contains high level of clay mineral as monmorillonite which has several properties. Before marketed is should be pulverized and packed. Pulverizing can be done traditionally by mean of using mortar as well as by modernly used mechanical grinder and vibrating discs mill. Effect of methods and duration of mechanical grinding on the characteristics of product including is structure, cathion exchange capacity and swelling index will be presented in this paper.Betonies was taken from Boyolaly-Central Java and pulveried traditionally as well as modernly in 2.5; 5.0; 7.5; 10 and 12.5 minuts. Alterations of its properties were analyzed, cathion exchange capacity and swelling index.Conclusion could be drawn that traditionally pulverizing did not affect on the structure of bentonie. However, the mechanical method using vibrating discs mill decrease the cathion exchange capacity, swelling index and cohesion forces might change the structure of montmorillonite from crystalline to amorf.